Study on Surrounding Rock Deformation Mechanism and Control of Roadway with Large Section and Extra-Thick Top Coal - Yuliang Yang (Shock and Vibration, 2021)
In order to solve the problem of safe and rapid excavation and support of roadway with large section and extra-thick top coal under complex geological conditions, the deformation mechanism and control of roadway are analyzed by means of field investigation, numerical simulation, theoretical analysis, and field practice, taking the 2203 transportation roadway of a mine in Shanxi Province as the engineering background. The results show the following: (1) the concentration of normal tensile stress in the middle of large-span roadway roof and end shear stress is significant, which may easily lead to the separation of roof and the extrusion deformation of surrounding rock; (2) the surface shear failure depth of the roadway side is large, and the insufficient length of the bolt, the small density of the protective side, and the insufficient support strength are easy to cause the bulge and splitting of the coal wall; (3) roof joints and fractures are developed, and the dirt band of different thickness occurs, so it is easy for the roof separation and the anchor solids to cut down along the weak surface of the dirt band; (4) the geological structure produces horizontal movement of surrounding rock, which easily leads to poor supporting effect of roadway roof and material deformation and failure. Finally, a safe and economic comprehensive support system of “high-strength, high-resistance, and high-prestressed anchor cable support system + high-strength support of the two sides roadway + U-shaped anchor cable combined truss” is proposed, and the control mechanism is explained and applied successfully in the field.